Milton's Paradise Lost comprehension through grammar - Poblete, Paz (Milaor) 1918- (1967)
Milton's Paradise Lost was taught in this study. It made use of grammar as a basic approach in teaching this English masterpiece to Filipino College students.
Thesis (M.A.T. English)--University of the Philippines, Diliman.
Keywords: Milton, John; Poetry -- Study and teaching